The inquisitorial censorship of “Vasconiana”, for two Cistercian monks of Fitero - Panizo Santos, Ignacio; Ostolaza Elizondo, Isabel (Huarte de San Juan. Geografía e Historia, 2010)
The aim of this article is to study, by means of the correspondence maintained between the Court of the Inquisition of Calahorra and the Counsel of the Inquisition, the focal point of witchcraft which emerged in Ochagavía and in other villages of the valley of Salazar at the beginning of 1539. Our goal, as well as to reconstruct the processes of faith initiated against the witches of Ochagavía, is to dissect the workings of the Inquisition in Navarre by relating the actions of the Court of the Inquisition of Calahorra not only to the judicial courts of Navarre, but also to the instructions and guidelines laid down by the Supreme Court and by other Counsels of the Spanish monarchy.
Keywords: Fitero Monastery; Inquisition; Literary censorship; Vasconiana; Banned books